PERANCANGAN SISTEM INFORMASI MANAJEMEN ASET DI KELURAHAN SUMUR PECUNG BERBASIS WEB - Widyawati Widyawati; Ahmad Surahmat; Rani Nadhiroh (Journal of Innovation And Future Technology (IFTECH), 2022)
Asset management is the management of asset data by grouping assets based on groups or recording assets in detail with the aim of organizing asset data so that they are well organized. Asset management in Serang City Village still uses conventional methods, especially asset management data collection in Sumur Pecung Village where the data collection still has several shortcomings and problems such as not explaining the layout of assets in detail, the layout of the location of assets, causing loss of one of the assets, the existence of duplicate data, lack of detailed information and poor data collection, namely data that is not integrated by inspectorate employees, especially every asset inspection report by inspectorate employees is not the same in writing this report format. This study aims to create an asset management information system by reducing problems that still use conventional methods. The data collection methods used are interviews, observation, and documentation to obtain accurate data. The software development used is the Waterfall model which is part of the System Development Life Cycle (SDLC) with stages of needs analysis, system design, implementation, integration and testing. Business process modeling uses the Unified Modeling Language (UML) with Use Case Diagram models, Activity Diagrams, and Sequence Diagrams. This information system which will later become a webbased application, was built using the Laravel Framework and several programming languages such as PHP, Java Script, CSS and MYSQL database. With this application, it can reduce asset management problems in Sumur Pecung Village in its data collection.